Quality of dialysis water and dialysate in haemodialysis centres: Highlight for occurrence of non-fermenting gram-negative bacilli - Anversa, Laís; Romani, Caroline D.; Caria, Eliane S.; Saeki, Erika K.; Nascentes, Gabriel A. N.; Garbelotti, Maricene; Stancari, Regina C. A.; Dantas, Stéfani T. A. [UNESP]; Rall, Vera L. M. [UNESP]; Ruiz, Luciana S.; Camargo, Carlos H.; Richini-Pereira, Virgínia B. (Oxford University Press (OUP), 2022)
Aims: To evaluate the physicochemical and microbiological quality of dialysis water and dialysate samples from haemodialysis centres. Methods and Results: Samples were fortnightly collected from three haemodialysis centres in Bauru City, Brazil, between July 2017 and June 2018, at the stages of post-reverse osmosis, reuse and dialysate. Analyses included determination of conductivity, fluoride, nitrate and sulphate; test for total coliform bacteria; count of heterotrophic bacteria; count and identification of non-fermenting gram-negative bacilli (NFGNB); drug susceptibility test; biofilm formation capacity; and genetic similarity among some isolated NFGNB. Of the analysed samples, only 4/72 (5.6%) had conductivity values ≥10 mS/cm, 4/216 (1.9%) presented total coliforms and 1/216 (0.5%) had heterotrophic bacteria count >100 CFU/ml. NFGNB were isolated from 99/216 (45.8%) samples, and the major identified micro-organisms included Herbaspirillum aquaticum/huttiense, Brevundimonas aurantiaca, Cupriavidus metallidurans, Pseudomonas aeruginosa and Ralstonia insidiosa. Isolates of P. aeruginosa and Burkholderia cepacia complex were sensitive to most antimicrobials and, together with isolates of Ralstonia insidiosa and Ralstonia pickettii, showed strong biofilm formation capacity. Some isolates expressed the same electrophoretic profile on pulsed-field gel electrophoresis, indicating the persistence of bacterial clones in the systems over time. Conclusions: NFGNB were observed in several dialysis water and dialysate samples from all investigated centres, which may represent a risk to the health of patients. Significance and Impact of the Study: Regular inclusion of actions for NFGNB control and monitoring in haemodialysis fluids are suggested for greater safety of the dialytic process.
Keywords: biofilm; dialysate; dialysis water; gram-negative bacteria; haemodialysis; susceptibility test